Meiocyte Isolation by INTACT and Meiotic Transcriptome Analysis in Arabidopsis - Barra, Lucia; Termolino, Pasquale; Aiese Cigliano, Riccardo; Cremona, Gaetana; Paparo, Rosa; Lanzillo, Carmine; Consiglio, Maria Federica; Conicella, Clara (Frontiers in Plant Science, 2021)
Isolation of nuclei tagged in specific cell types (INTACT) is a method developed to isolate cell-type-specific nuclei that are tagged through in vivo biotin labeling of a nuclear targeting fusion (NTF) protein. In our work, INTACT was used to capture nuclei of meiocytes and to generate a meiotic transcriptome in Arabidopsis. Using the promoter of AtDMC1 recombinase to label meiotic nuclei, we generated transgenic plants carrying AtDMC1:NTF along with biotin ligase enzyme (BirA) under the constitutive ACTIN2 (ACT2) promoter. AtDMC1-driven expression of biotin-labeled NTF allowed us to collect nuclei of meiocytes by streptavidin-coated magnetic beads. The nuclear meiotic transcriptome was obtained by RNA-seq using low-quantity input RNA. Transcripts grouped into different categories according to their expression levels were investigated by gene ontology enrichment analysis (GOEA). The most enriched GO term “DNA demethylation” in mid/high-expression classes suggests that this biological process is particularly relevant to meiosis onset. The majority of genes with established roles in meiosis were distributed in the classes of mid/high and high expression. Meiotic transcriptome was compared with public available transcriptomes from other tissues in Arabidopsis. Bioinformatics analysis by expression network identified a core of more than 1,500 genes related to meiosis landmarks.